Pengaruh Religiositas, Gaya Hidup dan Kualitas Produk terhadap Keputusan Pembelian Busana Muslim Nibras pada Nibras House di Lampung Selatan : Penelitian - Siti Nuraeni; Khil Wailmi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study is to partially and concurrently examine how Nibras consumers' shopping decisions at Nibras House, South Lampung, are influenced by their lifestyle, religion, and product quality. Purposive and non-probability sampling strategies are used in this quantitative survey-based research design. 150 respondents who are Nibras customers in South Lampung were given online questionnaires via Google Form in order to collect data. The analysis's findings indicate that the variables of religiosity (tcount of 8.446> t table 1.655), lifestyle (tcount of 7.902> t table 1.655), and product quality (tcount of 7.692> t table 1.655) all have positive and significant effects on purchasing decisions. The simultaneous hypothesis tests reveal that 152.677>ftabel 2.67. Y had a positive and statistically significant association with religious affiliation (X1), manner of life (X2), and product quality (X3), which operated separately or together